Breast stromal fibroblasts from histologically normal surgical margins are pro‐carcinogenic. Issue 4 (12th November 2013) - Al‐Rakan, Maha A; Colak, Dilek; Hendrayani, Siti‐Faujiah; Al‐Bakheet, Albandary; Al‐Mohanna, Falah H; Kaya, Namik; Al‐Malik, Osama; Aboussekhra, Abdelilah
Abstract: There is evidence that normal breast stromal fibroblasts (NBFs) suppress tumour growth, while cancer‐associated fibroblasts (CAFs) promote tumourigenesis through functional interactions with tumour cells. Little is known about the biology and the carcinogenic potential of stromal fibroblasts present in histologically normal surgical margins (TCFs). Therefore, we first undertook gene expression analysis on five CAF/TCF pairs from breast cancer patients and three NBF samples (derived from mammoplasties). This comparative analysis revealed variation in gene expression between these three categories of cells, with a TCF‐specific gene expression profile. This variability was higher in TCFs than in their paired CAFs and also NBFs. Cytokine arrays show that TCFs have a specific secretory cytokine profile. In addition, stromal fibroblasts from surgical margins expressed high levels of α ‐SMA and SDF‐1 and exhibited higher migratory/invasiveness abilities. Indirect co‐culture showed that TCF cells enhance the proliferation of non‐cancerous mammary epithelial cells and the epithelial‐to‐mesenchymal transition of breast cancer cells. Moreover, TCF and CAF cells increased the level of PCNA, MMP‐2 and the phosphorylated/activated form of Akt in normal breast luminal fibroblasts in a paracrine manner. Furthermore, TCFs were able to promote the formation and growth of humanized orthotopic breast tumours in nude mice. Interestingly, these TCF phenotypes and the extent of their effects were intermediate between those of NBFs and CAFs. Together, these results indicate that stromal fibroblasts located in non‐cancerous tissues exhibit a tumour‐promoting phenotype, indicating that their presence post‐surgery may play important roles in cancer recurrence. © 2013 The Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.